2005
DOI: 10.1159/000089294
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Secretory Regulation of Ghrelin during Growth Hormone Provocative Tests in Prepubertal Children with Various Growth Hormone Secretory Capacities

Abstract: Background and Objective: Ghrelin is a novel gastric peptide which stimulates GH secretion and has been demonstrated to have orexigenic and adipogenic properties. Insulin is a physiological and dynamic modulator of plasma ghrelin, and insulinemia possibly mediates the effect of the nutritional state on the plasma concentrations of ghrelin in adults. No data on the regulation of GH secretion by ghrelin have so far been reported, nor has the possible influence of hypoglycemia on the plasma ghrelin levels in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
1
14
1
1
Order By: Relevance
“…26 The present study demonstrated different ghrelin-GH responses in the two study groups. In accordance with Matsuoka et al, 12 an inverse association was noted between circulating GH and ghrelin levels in the NGH participants, indicating the presence of a negative feedback loop between GH and ghrelin. Moreover, NGH participants exhibited a decline in total ghrelin concentration prior to the GH peak.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…26 The present study demonstrated different ghrelin-GH responses in the two study groups. In accordance with Matsuoka et al, 12 an inverse association was noted between circulating GH and ghrelin levels in the NGH participants, indicating the presence of a negative feedback loop between GH and ghrelin. Moreover, NGH participants exhibited a decline in total ghrelin concentration prior to the GH peak.…”
Section: Discussionsupporting
confidence: 91%
“…[12][13][14][15] Two studies 12,26 have suggested an inverse relationship between circulating GH and ghrelin levels, indicating the existence of a feedback loop. Hirsh et al failed to relate ghrelin levels to the post-glucagon administration GH release, a finding explained by the authors as a result of the suppressed ghrelin exhibited after glucagon administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, there is a considerable amount of data in literature that does not support the possible "negative feed-back loop" of GH-IGF-I axis with ghrelin [33,34]. Only Matsuoka et al [35] with their very recent data were able to demonstrate such a negative feed-back loop. Another possible explanation could be that the suboptimal nutritional state in patients with short stature that ends up with lower height SDS could be the reason for the compensatory elevation of ghrelin as an orexigenic factor.…”
Section: Discussionmentioning
confidence: 97%
“…Although the physiological role of AG in the control of the somatotropic axis is probably less relevant than originally expected, anyway it remains that the exogenous administration of AG as well as its synthetic analogues such as hexarelin or GHRP6 represents one of the most potent pharmacological stimuli of GH secretion in humans in vivo (20,24,25).…”
Section: Introductionmentioning
confidence: 99%